La negociación del conflicto armado interno en Colombia: Dos escenarios probables y otro, posible pero improbable - Pérez Salazar, Bernardo (Sociedad y Economía, 2004)
Past failures and partial successes of peace settlement agreements with irregulararmed groups have been frequently overlooked in Colombia. Consequently lessons from these experiences have not been properly assimilated. The central scenario sketched in this article explores the the difficulties and possibilities of a “simultaneous peace settlement process” –breaking away from the “parcelled peace settlements” of the past– which would involve politically active social movements as well as all of the irregular armed groups in a peace settlement that might put a definite end to violent conflict in Colombia.